DEVELOPMENT OF SPEECH OF JUNIOR SCHOOLCHILDREN AS PSYCHOLOGICAL AND PEDAGOGICAL THIS METHODOLOGICAL PROBLEM (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the problem of speech development of junior schoolchildren; the different scientific approaches are analysed; the ways of language skills perfection of schoolchildren are suggested.